2015
DOI: 10.5901/mjss.2016.v7n1p258
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Structure on Banks Financial Performance by Moderating Firm Size

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
6
8
0
1
Order By: Relevance
“…The output indicates mixed results between the BOD characteristics and firm financial performance (ROA) where the BOD size on this occasion has a positive impact on firm financial performance (ROA). This outcome is similar as what has been found in other studies like [20,21].…”
Section: Roa = α0 + β1size + β2ceo + εsupporting
confidence: 93%
“…The output indicates mixed results between the BOD characteristics and firm financial performance (ROA) where the BOD size on this occasion has a positive impact on firm financial performance (ROA). This outcome is similar as what has been found in other studies like [20,21].…”
Section: Roa = α0 + β1size + β2ceo + εsupporting
confidence: 93%
“…It is henceforth of prime importance for banking institutions to mold their strategic resolutions while giving more attention to risk-return preferences controlled by bank size. Nodeh et al (2015) found that the size of banks had a moderating impact that was positive on the relationship between the determinants of structures of board and firms' financial performance depicting a consistent finding with the current study. Hanafi Tumin and Mohd Said (2010) deductions from the study indicated that size and level of liquidity in banks don't bear any influence that is significant on how banks perform in the two countries, which was contradictory with the findings depicted in the current study.…”
Section: Table 9 -Sargan Test For the Modelsupporting
confidence: 91%
“…In general terms, the relationship that exists between bank size of commercial banks and their performance is considered to be positive (Kiyota, 2011;Nodeh et al, 2015). However, several research studies have implicated bank size impact to be non-linear, with profitability increasing with commercial bank size and shrinking as a result of bureaucratic factors, among other reasons (Hanafi Tumin & Mohd Said, 2010).…”
Section: Table 9 -Sargan Test For the Modelmentioning
confidence: 99%
“…The positive effect outcomes indicated by board with more nonexecutive directors agree with the positive impact documented by Nwaubani (2019), Atuahene (2016), Dauda and Hawa (2016), Nodeh, Anuar, Suresh andRaftnia (2016, Hassan andFarouk (2014) but contradict the negative effect reported in Yilmaz and Buyuklu (2016), John (2015) and Olatunji and Ojeka (2011).…”
Section: Discussion Of Findingssupporting
confidence: 63%
“…The study recommended that the board size should be limited to a sizeable number and the audit committee be composed of mainly directors with adequate skills, and who are familiar with the banking terrain. Nodeh, Anuar, Suresh and Raftnia (2016) evaluated the role of bank size as moderator on relationship between board independence and board size with banks financial performance using the data of 37 Malaysian banks. The results revealed that board independence and board size have positive impact on firm financial performance.…”
Section: Journal Of Public Management Researchmentioning
confidence: 99%